OPTIMIZING THE ROLE OF TECHNOLOGY IN MADRASAH: TOWARDS A MODERN RELIGIOUS EDUCATION - Ahmad Kudori; Muslimin; Halimatus Sa'diyah (CV. ADIBA AISHA AMIRA, 2023)
The use of technology in madrasas can bring many benefits, including improving access to education, improving the quality of learning, facilitating communication, and improving administrative efficiency. However, there are also challenges to overcome, such as the availability of adequate infrastructure and resources, the training and understanding of teachers, security and privacy concerns, and compliance with existing religious curricula. By addressing these challenges, the madrasah can optimize the use of technology in religious education. This can lead to improvements in the quality of education, student capacity, and learning experience in the Madrasah. Nevertheless, it is important to ensure that the application of technology at the matrasah is consistent with the sacred principles of religious teaching, so that technology can be a tool that supports and enriches religious learning. Thus, overall, the optimization of technology can produce modern, relevant, and high-quality religion education for the students